Evaluasi Pengendalian Intern Terhadap Sistem Akuntansi Pembelian dan Persediaan Bahan Baku Pada PT Fuyindo Multi Perdana - Mariani, Vini; Bindari, Yonarsie (Bina Nusantara University, 2010)
Internal control is essential for the operational activities of a company. The author conducted research for internal control of accounting systems and inventory purchases of raw materials. Internal controls for purchasing and inventory of raw materials is essential if companies want to produce a superior product. In this study researchers prepare the field research method by observation and literature study by studying the theories associated with the purchase and supply of raw materials. The results obtained show the important things that can be controlled by the company for operating companies to run well and the management can give a decision based on the reports of evaluation results, it can be suggested that companies should do in the internal control system purchase accounting and inventory of raw materials.